“ MELESTARIKAN PERMAINAN TRADISIONAL SIKIDOKA, GALA ASIN DAN BOLA KASTI DI ERA REVOLUSI INDUSTRI 5.0” - Sam Nubatonis; Ardi Y. Tafuy; Migdes C. Kause; Figinus K. Dawi; Yohanes A. Seran; Rivaldo Crise Knaufmone; Nani Serezy Selan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This dedication raises the importance of preserving traditional games in the modern era as it is today. Traditional games have many benefits, apart from being a nation's cultural heritage, traditional games can also act as a tool to train children's motor development, children's social interaction skills, and also character formation in children. The implementation method used is outreach and direct practice in the field. Seeing what is happening now, where children are more interested in digital games that do not train children's personal development makes them worry about the future of the nation's successors in the future. So that this activity of introducing traditional games really needs to be done considering the many benefits that can be obtained as well as to participate in preserving traditional games which have become cultural heritage in Indonesia.